The QRIS Effect: What Truly Motivates MSMEs to Go Digital? - Fauziah , Kinkan Wandana Ayu; Juwiyan, Yowelcy Lovea; Lestari, Made Irma; Kurniawati , Heny; Deviarti, Holly (Airlangga Journal of Innovation Management, 2025)
QRIS is now usable in several countries through partnerships,enabling Rupiah-based transactions abroad. This study aims to determine the analysis of the effect of QRIS fees, transaction security, service benefits and ease, and use on interest in using QRIS in buying and selling transactions for MSMEs in Indonesia. This study uses primary data obtained from the collection method on a questionnaire with sampling by purposive sampling method. The questionnaire was randomly distributed online to MSMEs in Indonesia. The questionnaire contains items that need to be completed and sent using the google forms platform. As much as 100 data samples tested with data analysis using the Structural Equation Model (SEM) method through the Partial Least Squares (PLS) approach by conducting a convergent validity test, a discriminant validity test, a reliability test, a determination coefficient test (R2), and a path coefficient test. The results showed that QRIS fees, transaction security, service benefits and ease, and use simultaneously had positive and significant effects on interest in using QRIS in buying and selling transactions for MSMEs in Indonesia. Bank Indonesia needs to pay attention to these factors in the broader implementation of QRIS. It needs more promotion to introduce the benefits of QRIS usage for Indonesian MSMEs. This research provides help to policymakers develop QRIS.